Value propositions of the water footprint concept for sustainable water utilities - Badruzzaman, Mohammad; Hess, Tim M.; Smith, Heather M.; Upson, Sophie; Jacangelo, Joseph G. (American Water Works Association (AWWA), 2017)
The water footprint concept has been used by agricultural, commercial, and industrial water users to measure and report their water consumption, assess the magnitude of potential environmental impacts arising from this consumption, and identify opportunities for risk mitigation strategies that promote sustainable water use. However, water and wastewater utilities have not studied and documented the application of this concept in the same manner that other industries have. This article summarizes the growing body of information on the water footprint concept and the opportunities for integrating the concept into water utility planning efforts as a broader means of achieving and maintaining sustainable communities. The application of the water footprint concept for capital improvement planning, water resources decision-making, operational benchmarking, and stakeholder communications is discussed, as is how the methodology, developed by the International Organization for Standardization, can be used for a water utility.
Keywords: environmental impact; ISO14046; life cycle assessment; water